Identification of Health Problems in Ngasem Village Selomartani Kalasan Sleman Yogyakarta 2019 - Subagyono (Journal of Medical Laboratory in Infectious and Degenerative Diseases, 2023)
Background: Health is the right of every citizen. Problem identification is the first step in determining problem priorities. Kalasan District is one of the sub-districts in Sleman Regency, Yogyakarta which still has health problems, especially Noncommunicable diseases, Healthy Behavior, and environmental.Purpose: This study aims to analyze the factors that cause health problems, especially the problem of non-communicable diseases in the community, and determine the priority of existing problems in Kalasan District, Ngasem Hamlet, Neighbourhood 001, 002, 003, and 004.Methods: This research is an analytical observational study with Community Development Practice study design. The research sample was residents of Ngasem Hamlet RT 001, RT 002, RT 003, and RT 004 totaling 139 families who were determined using accidental sampling techniques. Data analysis was carried out using univariate analysis and priority analysis using the ultrasound method using scoring techniques (Urgency, Seriousness, and Growth).Results: The results of the analysis using the ultrasound method show that the priority problem (I) is hypertension with a total score of 14, the second priority problem (II) is the distance between the Waste Water Management System and the water source <10 m with a score of 10, and the third priority problem (III) is smoking behavior with score 9.Conclusions: It can be concluded that the priority health problems found are hypertension, smoking behavior and the distance of SPAL from water source <10 m.